A View Into Successful Teaching Techniques: Teaching Malay Language As A Foreign Language In Malaysia - Baharudin, Mazlina; Md Sadik, Azlina (Dinamika Ilmu, 2016)
This paper will highlight successful teaching techniques used in class in teaching the Malay Language 1 course in Universiti Sains Malaysia (USM). The course is to equip foreign students for their studies and also as means of basic communication with the locals in Malaysia. In Malaysia, the emphasis in Malay language teaching are focused to Malaysians and had been on grammar structure. There has been little development of teaching of Malay as a foreign language. However, the effort to introduce Malay as a foreign language is important since generally there are a growing number of learners who are aware of the benefits. Other than travelers guide and basic Malay phrase books, not many materials are found for teaching of Malay as a foreign language. Based on the lack of resources, teachers have to incorporate techniques to be used in class to teach the Malay language course. It is hoped that other foreign language teachers will find information useful especially in the teaching the Malay Language as a foreign language.